Effects of ethylenediamine to water ratios on cadmium sulfide nanorods and nanoparticles produced by a solvothermal method - Phuruangrat A. (2014)
Cadmium sulfide nanorods and nanoparticles were successfully produced by a solvothermal reaction at 200 °C for 24 h using ethylenediamine and water as pure and mixed solvents. The products were analyzed by X-ray diffraction, Raman spectroscopy and transmission electron microscopy. In pure ethylenediamine, they show the hexagonal structure CdS nanorods with 0.2-2 μm long and 30 nm diameter, and the 1LO and 2LO modes at 299.36 and 600.72 cm- 1, respectively. Growth of CdS nanorods is along the [001] direction, interpreted by HRTEM images and SAED patterns. In the 50:50 vol.% of ethylenediamine:water mixed solvents, the length of CdS nanorods decreased to 100-200 nm. The CdS nanoparticles were produced when pure water was used. © 2009 Elsevier B.V. All rights reserved.